2020
DOI: 10.1508/cytologia.85.239
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Heavy Metals on Mung Bean (<i>Vigna radiata</i>) Seedlings and Its Alleviation by Priming with Their Lower Concentrations

Abstract: Due to urbanization and industrialization, heavy metals have become the common environmental pollutant throughout the world. Chromosomal studies are one of the important tools to estimate the genome damaging property of these metals. This research was done to analyze the genotoxic effects of metals such as cadmium (Cd), nickel (Ni), mercury (Hg), lead (Pb) and copper (Cu) in mung bean (Vigna radiata) root tips. The experiment was set in such a way that mild metal treatment (0.01 mM) was given before respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In our study, the mitotic index decreased in the treatment groups compared with control group plants. Similar results were reported by Bhattacharjee et al [41] after exposure of the green alga Chara vulgaris to indigo carmine for 6 h. Also, a decrease in the mitotic index in treatment groups after exposure to different toxics has been reported previously [43,45,54,58,61,64,[69][70][71][72][73][74][75]. In our study, no dependence was observed between the concentration of indigo carmine and the effects on the mitotic index or mitotic inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the mitotic index decreased in the treatment groups compared with control group plants. Similar results were reported by Bhattacharjee et al [41] after exposure of the green alga Chara vulgaris to indigo carmine for 6 h. Also, a decrease in the mitotic index in treatment groups after exposure to different toxics has been reported previously [43,45,54,58,61,64,[69][70][71][72][73][74][75]. In our study, no dependence was observed between the concentration of indigo carmine and the effects on the mitotic index or mitotic inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, genotoxicity is a proven adverse effect elicited by heavy metals exposure. Cadmium (Cd), arsenic (As), and lead (Pb) all have been shown to cause several genetic abnormalities, such as micronucleus formation, chromosomal abnormalities, and DNA damage [ 12 , 13 , 14 ]. Since genotoxicity is the prerequisite for the incidence of most malignancies, a series of heavy metals have been classified as Group I carcinogenic agents by the International Agency for Rese [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA is constantly exposed to exogenous stimuli, such as ultraviolet (UV) or gamma radiation (Takahashi et al 2019, Suto et al 2020, environmental pollution (Basu et al 2019, Hani et al 2020, artificial chemicals (Ergin et al 2020, Gantayat et al 2020, chemotherapeutic drugs (Gupta et al 2020), dietary genotoxins, and endogenous stimulants during physiological cellular processes (Jackson and Bartek 2009, Paigen and Petkov 2010, Diaz and Pecinka 2017, Tubbs and Nussenzweig 2017, Toyoda and Matsunaga 2019, Marques et al 2020, Mingard et al 2020, Nishioka et al 2020. These stimulants are known to induce approximately 70,000 lesions every day in each human cell, including single-strand breaks (SSBs) and double-strand breaks (DSBs), which are essentially fixed via various DNA repair pathways (Kunkel 2015, Tubbs andNussenzweig 2017); however, sometimes DNA damage is not repaired correctly, and the accumulation of these unrepaired damages is known to cause various pathological conditions, such as premature aging, cancer, and neurological disorders (Lord and Ashworth 2012, Baranello et al 2014, Canela et al 2016, González and Plasencia 2017.…”
mentioning
confidence: 99%